Factors influencing the level of job satisfaction of employees as the main internal stakeholders of organizations in the 21st century - Igielski, Michał (Zielona Góra: Faculty of Economics and Management Press)
The main purpose of the article is to identify the main factors that have the greatest impact on building satisfaction of employees who work in Polish organizations. In addition, the author will try to identify the expectations of respondents that apply to their workplaces and identify the most important problems and barriers in the surveyed organizations, occurring in the processes of human capital management. As the main research method, in addition to the literature analysis, of course, the author chose a survey, in the form of a structured interview, with team leaders and their employees.
Keywords: stakeholders; job satisfaction; employee expectations